Descriptive Approach of Neo-Banking System: Conception, Challenges and Global Practices - Alaeddine Ziouache; Mohamed Bouteraa (Asian Scholars Network, 2023)
The massive growth in demand for new technologies and applications in the banking sector has consequently heightened consumer concern about Neo-banks systems. A neo bank is a type of direct bank that operates exclusively using online banking without traditional physical branch networks that challenge traditional banks. This article primarily attempts to review the literature on Neo-banking and its practices. It has also highlighted the main initiatives, benefits, challenges, of Neo-banks systems globally. Furthermore, this study aimed to provide a theoretical discussion of Neo-banking by extending the TAM Model by security and trust to determine the identify the factors affecting users’ perception. It is found that there green banking is essential in the current global digital economy and the advances of technology and artificial intelligence. Therefore, considerable initiatives have been taken in the world in this regard by the banks and governments, but Neo-banks systems is still ay primary stage due to the low adoption by the consumer.